2018
DOI: 10.1248/cpb.c17-00854
|View full text |Cite
|
Sign up to set email alerts
|

Linear Discriminant Analysis for the <i>in Silico</i> Discovery of Mechanism-Based Reversible Covalent Inhibitors of a Serine Protease: Application of Hydration Thermodynamics Analysis and Semi-empirical Molecular Orbital Calculation

Abstract: We recently reported that the Gibbs free energy of hydrolytic water molecules (ΔG) in acyl-trypsin intermediates calculated by hydration thermodynamics analysis could be a useful metric for estimating the catalytic rate constants (k) of mechanism-based reversible covalent inhibitors. For thorough evaluation, the proposed method was tested with an increased number of covalent ligands that have no corresponding crystal structures. After modeling acyl-trypsin intermediate structures using flexible molecular super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Despite using training set and test set compounds that would more appropriately be described as competitive substrates, the model still provides useful information demonstrating that (intuitively) both the lower Gibbs free energy of water and the increased activation energy for bond-cleavage lead to a slower reverse reaction of the covalent adduct. In their work, the entropic component of the Gibbs free energy equation (-TΔ S ) correlates well with k cat , suggesting that their model utilizing the Gibbs free energy of water and the activation energy of covalent–adduct bond cleavage may be effective parameters by which to discriminate covalent inhibitors . Efforts by Chatterjee et al have been to probe free energy perturbations using quantum mechanics/molecular mechanics (QM/MM) calculations to predict binding affinities and binding kinetics for warheads and their target enzymes.…”
Section: Modeling In Covalent Inhibitor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite using training set and test set compounds that would more appropriately be described as competitive substrates, the model still provides useful information demonstrating that (intuitively) both the lower Gibbs free energy of water and the increased activation energy for bond-cleavage lead to a slower reverse reaction of the covalent adduct. In their work, the entropic component of the Gibbs free energy equation (-TΔ S ) correlates well with k cat , suggesting that their model utilizing the Gibbs free energy of water and the activation energy of covalent–adduct bond cleavage may be effective parameters by which to discriminate covalent inhibitors . Efforts by Chatterjee et al have been to probe free energy perturbations using quantum mechanics/molecular mechanics (QM/MM) calculations to predict binding affinities and binding kinetics for warheads and their target enzymes.…”
Section: Modeling In Covalent Inhibitor Designmentioning
confidence: 99%
“…In their work, the entropic component of the Gibbs free energy equation (-TΔ S ) correlates well with k cat , suggesting that their model utilizing the Gibbs free energy of water and the activation energy of covalent–adduct bond cleavage may be effective parameters by which to discriminate covalent inhibitors. 19 Efforts by Chatterjee et al have been to probe free energy perturbations using quantum mechanics/molecular mechanics (QM/MM) calculations to predict binding affinities and binding kinetics for warheads and their target enzymes. They found that using this approach, when covalent binding was 5.5 kcal/mol stronger than noncovalent binding, selectivity could be predicted by the relative free binding energy of the covalent state.…”
Section: Modeling In Covalent Inhibitor Designmentioning
confidence: 99%